Beyond Uncertainty : Heisenberg, Quantum Physics, and The Bomb. - Cassidy, David C. (Bellevue Literary Press, 2010)
Award winning biographer revisits the controversial life of this well known German physicist to shed new light on troubling questions. What can we learn about the relationship of scientific research to state power from Heisenberg's role in Nazi Germany?